A CAST-based causal analysis of the catastrophic underground pipeline gas explosion in Taiwan. (January 2020) - Li, Feng; Wang, Wenhe; Xu, Jiang; Dubljevic, Stevan; Khan, Faisal; Yi, Jun
Highlights: The study originally adopts the CAST model to pipeline gas transportation industry. The causes of the pipeline gas explosion in Taiwan are analyzed based on CAST. The safety control structure to enforce the safety constraints is developed. The safety control structure is analyzed hierarchically. The CAST model is feasible for continuous improvements in safety management. Abstract: A deep and thorough analysis of typical accidents beyond immediate failures from a systematic perspective is necessary for safety decision-making in an area. The Systems-Theoretic Accident Model and Processes (STAMP) is one of the most widely used accident models based on systems and control theory, which derives a powerful accident analysis tool defined as Causal Analysis based on Systems Theory (CAST). This study adopts a CAST analysis of the catastrophic underground pipeline gas explosion in Taiwan, which is one of the largest petroleum catastrophes in Chinese history. The safety control structure to enforce the safety constraints required by the system hazards is developed and analyzed hierarchically. The analysis has systematically demonstrated the inadequate control and violated safety constraints and uncovered the in-depth rationale behind the decisions that were made leading up to this tragedy. The necessary changes in the overall system safety structure are also recommended based on control flaws identified for each hierarchical level, accordingly. The CAST model is demonstrated to be feasible for continuous improvements in accident analysis and in turn establishing a robust safety system of pipeline gas transportation in Taiwan.